Clarifying boundaries of binge eating disorder and psychiatric comorbidity: a latent structure analysis. - Hilbert, A; Pike, K; Wilfley, D; Fairburn, C; Dohm, F; Striegel-Moore, R (2011)
Binge eating disorder (BED) presents with substantial psychiatric comorbidity. This latent structure analysis sought to delineate boundaries of BED given its comorbidity with affective and anxiety disorders. A population-based sample of 151 women with BED, 102 women with affective or anxiety disorders, and 259 women without psychiatric disorders was assessed with clinical interviews and self-report-questionnaires. Taxometric analyses were conducted using DSM-IV criteria of BED and of affective and anxiety disorders. The results showed a taxonic structure of BED and of affective and anxiety disorders. Both taxa co-occurred at an above-chance level, but also presented independently with twice-as-large probabilities. Within the BED taxon, diagnostic co-occurrence indicated greater general psychopathology, lower social adaptation, and greater premorbid exposure to parental mood and substance disorder, but not greater eating disorder psychopathology. Eating disorder psychopathology discriminated individuals in the BED taxon from individuals in the affective and anxiety disorders taxon. Diagnostic criteria of BED were more indicative of the BED taxon than were criteria of affective and anxiety disorders. The results show that at the latent level, BED was co-occurring with, yet distinct from, affective and anxiety disorders and was not characterized by an underlying affective or anxiety disorder.